2021
DOI: 10.1007/s42452-021-04498-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the status of land use/land cover change using remote sensing and GIS in Jewha Watershed, Northeastern Ethiopia

Abstract: Evaluation of land use/land cover (LULC) status of watersheds is vital to environmental management. This study was carried out in Jewha watershed, which is found in the upper Awash River basin of central Ethiopia. The total catchment area is 502 km2. All climatic zones of Ethiopia, including lowland arid (‘Kola’), midland semi-arid (‘Woinadega’), humid highland (Dega) and afro alpine (‘Wurch’) can be found in the watershed. The study focused on LULC classification and change detection using GIS and remote sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…About, 3616.45 ha of this land were converted to cultivation land and settlement area. This study is in agreement with some of the studies in Ethiopia where a significant change of grassland into cultivation land[2,20,24,70]. All these studies reported in their respective found that local communities are converting grassland into cultivation land to satisfy the need of the ever growing population.Forest Land (FL):FL was the largest LULC class, with the share of 3287.79 ha (9.52 %) of the total area of the study area in 1974 (Table6).…”
supporting
confidence: 92%
“…About, 3616.45 ha of this land were converted to cultivation land and settlement area. This study is in agreement with some of the studies in Ethiopia where a significant change of grassland into cultivation land[2,20,24,70]. All these studies reported in their respective found that local communities are converting grassland into cultivation land to satisfy the need of the ever growing population.Forest Land (FL):FL was the largest LULC class, with the share of 3287.79 ha (9.52 %) of the total area of the study area in 1974 (Table6).…”
supporting
confidence: 92%
“…It is a crucial way human activities affect ecosystems (Li et al., 2018). Over recent decades, LULC has been substantially changed ( Belay and Mengistu, 2019 ; Betru et al., 2019 ; Habte et al., 2021 ; Sisay et al., 2021 ), which have had an incredible impact on ecosystem services by influencing ecosystem patterns and processes ( Gashaw et al., 2018 ; Kindu et al., 2016 ). Humans benefit directly from changing land use types but dramatically alter ecosystem services.…”
Section: Introductionmentioning
confidence: 99%
“…The percent and rate of changes in LULC in the Ajora-Woybo watershed from 1990to 2000, 2000to 2010, 2010, and 1990 contributed to the expansion of various land-use types (Gashaw et al, 2017;Habte et al, 2021;Leta et al, 2021;Tadese et al, 2021).…”
Section: F I G U R Ementioning
confidence: 99%
“…In addition, they determined that intensive agriculture with poor management methods is a widespread problem in the watershed. Furthermore, different studies revealed that population pressure, various agricultural techniques, urbanization, drought frequency, and poor land use planning, as well as institutional and environmental challenges, were the primary reasons of land use change in Ethiopia (Dagnachew et al, 2020;Dibaba et al, 2020a;Ewunetu et al, 2021;Fasika et al, 2019;Gashaw et al, 2017;Habte et al, 2021;Hassen & Assen, 2018;Tadese et al, 2020Tadese et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%